Effect of Styrene Butadiene Rubber Latex on Mechanical Properties of Eco Concrete: Limestone Powder Concrete - Al Numan, Bayan S.; Ahmed, Faris R.; Hamad, Kamaran K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
To make concrete a truly green material, viable cement substitutes are available. This experimental investigation is performed to study the effect of using limestone powder (LSP) and styrene butadiene rubber (SBR) latex in the concrete mix. In this work, a concrete with 1:1.8:3 cementitious material:sand:gravel and water/cement ratio w/c of 0.5 is produced. First, LSP is used with 0, 5, 10, 15, and 20% replacements by weight of cements. The fineness of the LSP is measured using sieve No. 200 and showed about 30% pass. Second, and to improve the matrix of concrete due to the dilution effect, four ratios of SBR latex (0, 5, 10, and 15%) are added by weight of cements to the mix for each LSP ratio. Compressive strength at ages of 3, 7, 14, 28, and 90 days is tested for the concrete specimens mixed with LSP only to examine its effect on concrete strength’s development with time, whereas strengths are recorded at the age of 28 days for the other concretes. Three prisms were cast for each ratio and tested at 28 days. The results show general improvements in terms of compressive and flexural strengths.